COVID-19 and Pet Animals: What we need to know? (Research in Agriculture Livestock and Fisheries, 2020)
The virus COVID-19 (SARS-CoV-2) seems to be emerged initially from an animal source, but the current spread of COVID-19 is a result of human-to-human transmission. To date, according to the World Health Organization (WHO) “there is no evidence that a dog, cat or any livestock can transmit COVID-19”. During this pandemic emergency, animals and people each need the support of the other. Therefore, the World Organisation for Animal Health (OIE) stress that, at this time, as always, “it is important not to give in to anxiety and to keep on providing loving care for our pets”. So, there is no justification in taking measures against companion animals, which may compromise their welfare.Res. Agric., Livest. Fish.7(1): 83-86, April 2020